Influencing Factors Telkomsel Internet Package Purchase Decision - Muhammad Zulkarnain; Mukarramah (LPPM Universitas Respati Indonesia, 2024)
The study aims to determine the factors that influence the decision to purchase Telkomsel internet packages in Langsa. The study used a sample of 96 respondents who were Telkomsel internet package users in Langsa City. The data analysis method uses validity, reliability, classic assumption test, multiple linear regression test, coefficient of determination test (R2) and hypothesis test. The results obtained from three factors namely product quality, price and brand image have a positive and significant effect on the decision to purchase Telkomsel internet packages. The coefficient of determination test results obtained by 0.531 or 53.1 product quality, price and brand image affect the purchase decision of Telkomsel internet packages and the remaining 46.9% is influenced by other variables not examined. Keywords: Product Quality, Price, Brand Image, Purchasing Decision